Productivity and Physicochemical Properties of the BRS Isis Grape on Various Rootstocks under Subtropical Climatic Conditions - Sánchez, Camilo André Pereira Contreras [UNESP]; Tecchio, Marco Antonio [UNESP]; Callili, Daniel [UNESP]; da Silva, Marlon Jocimar Rodrigues [UNESP]; Basílio, Leticia Silva Pereira [UNESP]; Leonel, Sarita [UNESP]; Alonso, Juan Carlos [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (MDPI, 2023)
Brazil has emerged as a significant producer of seedless grapes due to high consumer demand. This has led to increased production of seedless grapes in non-traditional cultivation regions, such as subtropical areas. To meet this demand, the search for new grape varieties suitable for these conditions, such as the ‘BRS Isis’ variety, has become an option for growers. The interaction between grape cultivars and rootstocks is specific, and their adaptability to climatic conditions can result in uneven performance. Therefore, the choice of rootstock should be considered before making any recommendations. The purpose of this study was to assess the productive performance, physical-chemical, and biochemical properties of the ‘BRS Isis’ vine grafted onto rootstocks (‘IAC 572’, ‘IAC 766’, and ‘Paulsen 1103’) in two production cycles. The experimental design consisted of randomized blocks, with seven blocks and three plants per plot, for a total of 63 vines. Thus, the vine’s income components, physical qualities of bunches and berries, chemical profile, bioactive substances, and antioxidant activity were assessed. The Tukey test (5% probability) was used to compare means between rootstocks. The data on scion cultivar and rootstock pairings were further evaluated using principal component analysis (PCA). There were substantial variations in the rootstocks, with ‘IAC 572’ and ‘IAC 766’ producing more bunches, generating more fresh mass, and having a longer bunch length than ‘Paulsen 1103’. However, phenolic compounds and flavonoids were greater in ‘BRS Isis’ grapes than in ‘Paulsen 1103’. ‘BRS Isis’ shows good adaptation to subtropical environments when employing the IAC 572 and IAC 766 rootstocks due to their higher yield and bioactive component accumulation compared to grapes grafted onto ‘Paulsen 1103’. However, regardless of the rootstock utilized, ‘BRS Isis’ grapes perform well commercially in subtropical environments.